CHARACTERISTICS OF THE SCIATIC NERVE TRUNK STRUCTURAL COMPONENTS WITH ADMINISTERING THE CRYOPRESERVED PLACENT IN RATS - Sviridyuk, R.V.; Shepitko, V.I.; Shepitko, K.V.; Klypachenko, I.V. (World of Medicine and Biology, 2018)
Peripheral nerves injuries by various factors is an actual problem of modern practical and experimental medicine. When inflammatory process affects peripheral nerves, treatment and rehabilitation of such patients takes a long time. The purpose of the study was to establish changes in the morphometric parameters of the sciatic nerve trunk structural elements in rats with a single-dose subcutaneous administration of the cryopreserved placenta. The sciatic nerve trunk was removed from 50 sexually mature rat males of the “Wistar” line. Using a microscope with a digital microphotography, morphometry of the following indices was performed: total thickness of the sciatic nerve, thickness of the epineurium, thickness of the perineurium, thickness of the endoneurium. The trunk of the sciatic nerve consists of an epineurrium that covers the trunk; perineurium - longitudinally oriented collagen (elastic) fibers that act as a membrane; endoneurium, which covers bundles of myelin fibers. It was found that the morphometric parameters of the sciatic nerve trunk grew due to the intercellular space exudation. On the 1st, 2nd, 3rd, and 5th days of the experiment, the total thickness of the sciatic nerve trunk was thickened by 2.8%, 3.4%, 8.2%, 3.5% at (p